Leather Industry in Bangladesh: Opportunities and Challenges - Khan, Wahiduzzaman (American Journal of Trade and Policy, 2014)
Leather is a unique commodity that links grassroots villages with high societies and traditional practices with emerging technologies. For many developing countries, leather and leather manufacturers constitute an indispensable and dependable source for export trade and foreign exchange earnings. For Bangladesh, leather is a high priority industrial sector and footwear exports, an extreme focus area. Bangladesh has, just few decades since Independence, made significant gains from the leather trade, progressing from the status of an exporter of 90% plus raw hides and skins to that of an exporter and predominantly leather product manufacturer. However, there is little systematic research into this sector. This study is trying to address the research gap by seeking to understand the current status, problems and prospect of leather industry in Bangladesh.
Keywords: Leather Industry; Problems and prospects; Bangladesh